Legal Approaches to Healthcare Bankruptcy: A Comparative Study - Muhammad Fitratallah Dahlan; Nurisnah H; Hilmiah (Ekasakti Jurnal Penelitian dan Pengabdian, 2026)
The intersection between bankruptcy law and health law has become increasingly significant as hospitals experience financial distress that may lead to insolvency. In such circumstances, safeguarding patient rights emerges as a critical legal concern. This study aims to examine how patient rights are regulated and protected during hospital bankruptcy across several jurisdictions. This research employs normative legal research using a qualitative approach, focusing on the analysis of statutory regulations, legal principles, and comparative legal doctrines in the United States, Europe, Japan, and Indonesia. The findings reveal that each jurisdiction adopts distinct legal mechanisms to balance financial restructuring with patient protection. The United States appoints a Patient Care Ombudsman under Chapter 11 to supervise healthcare quality during bankruptcy proceedings. Several European countries emphasize strict regulatory safeguards to ensure continuity of medical services, while Japan provides alternative restructuring mechanisms to prevent service disruption. In contrast, Indonesia’s Bankruptcy Law (Law No. 37 of 2004) lacks specific provisions addressing hospital insolvency, resulting in legal uncertainty and limited protection for patients. Therefore, comprehensive reform is necessary to integrate patient protection principles into Indonesia’s bankruptcy regime and to ensure the effective protection of the right to health.